Peroxisome Proliferator-Activated Receptor α Activation Protects Retinal Ganglion Cells in Ischemia-Reperfusion Retinas - Yao, Fei; Zhang, Xuan; Yao, Xueyan; Ren, Xiaohua; Xia, Xiaobo; Jiang, Jian; Ding, Lexi (Frontiers in Medicine, 2021)
Background and Objective: Retinal ischemia-reperfusion (IR) leads to massive loss of retinal ganglion cells (RGCs) and characterizes several blind-causing ophthalmic diseases. However, the mechanism related to retinal IR is controversial, and a drug that could prevent the RGCs loss caused by IR is still lacking. This study aimed to investigate the role of endogenous retinal peroxisome proliferator-activated receptor (PPAR)α and the therapeutic effect of its agonist, fenofibric acid (FA), in IR-related retinopathy. Material and methods: FA treatment was applied to the Sprague–Dawley rats with IR and retinal cell line 28 cells with oxygen-glucose deprivation (an in vitro model of IR). Western blotting, real-time PCR, and immunofluorescence were used to examine the expression levels of PPARα, glial fibrillary acidic protein (GFAP), and cyclooxygenase-2 (COX2). HE staining, propidium iodide staining, retrograde tracing, and flash visual-evoked potential were applied to assess RGCs injury and visual function. Results: Retinal IR down-regulated PPARα expression in vitro and in vivo. PPARα activation by FA promoted survival of RGCs, mitigated thinning of the ganglion cell complex, and decreased the latency of positive waves of flash visual-evoked potentials after IR injury. Further, FA treatment enhanced the expression of endogenous PPARα and suppressed the expression of GFAP and COX2 significantly. Conclusion: PPARα activation by FA is protective against RGCs loss in retinal IR condition, which may occur by restoring PPARα expression, inhibiting activation of glial cells, and suppressing retinal inflammation. All these findings indicate the translational potential of FA in treating IR-related retinopathy.